1991
DOI: 10.1002/hed.2880130405
|View full text |Cite
|
Sign up to set email alerts
|

Induction intra‐arterial cisplatin and bleomycin in head and neck cancer

Abstract: Fifty-two consecutive patients, affected by large T2 (greater than 3 cm), T3, T4, N0, or N1 previously untreated squamous cell carcinoma of the head and neck, entered this phase I-II study. Treatment consisted of a continuous 8-day infusion on the following daily schedule: cisplatin 25 mg and bleomycin 15 mg administered for 4 and 20 hours, respectively. Technical-related toxicities were 1 case each of coagulation and displacement of the catheter and 1 case of reversible monoparesis of the contralateral arm. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Transcatheter arterial infusion therapy, which allows concentrated drugs to be distributed throughout a target organ, is expected to improve therapeutic effects while reducing adverse reactions of other organs to the drug (9, 10). In recent years, transcatheter arterial infusion therapy has been performed for various diseases such as severe pancreatitis using protease inhibitor and antibiotics (11), inflammatory bowel disease using steroids (12), and malignant tumors of the liver (1317), urinary bladder (18), uterus (19), and head and neck (20) using anticancer drugs. TASIT is a novel method, designed for treating SAHF by Koto et al , based on the finding that intrahepatic macrophage activity in patients with SAHF is suppressed by corticosteroids (21, 22).…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter arterial infusion therapy, which allows concentrated drugs to be distributed throughout a target organ, is expected to improve therapeutic effects while reducing adverse reactions of other organs to the drug (9, 10). In recent years, transcatheter arterial infusion therapy has been performed for various diseases such as severe pancreatitis using protease inhibitor and antibiotics (11), inflammatory bowel disease using steroids (12), and malignant tumors of the liver (1317), urinary bladder (18), uterus (19), and head and neck (20) using anticancer drugs. TASIT is a novel method, designed for treating SAHF by Koto et al , based on the finding that intrahepatic macrophage activity in patients with SAHF is suppressed by corticosteroids (21, 22).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with previously untreated disease, the average overall and complete response rates in 85 patients treated with cisplatin alone from three collected studies were 76.5% (range, 70.8% to 82%) and 29.9% (range, 24.2% to 32%), respectively 11‐13 . The average overall and complete response from IA cisplatin combined with one or more other drugs was 78.5% (range, 46% to 94%) and 21.6% (range, 7.7% to 43%), respectively, in 167 patients with previously untreated disease collected from six studies 11,14‐18 . The results from the IA trials are variable, but several studies, particularly those using cisplatin‐based regimens, indicate that a high response rate can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors subsequently reported on the use of intra-arterial chemotherapy alone, but CR rates remained disappointingly low, in the range of 7.7%-33% [27][28][29][30][31]. The main criticism leveled at regional chemotherapy techniques was that there was no clear survival benefit over conventional systemic chemotherapy but a considerably greater risk of local toxicity.…”
mentioning
confidence: 99%